A retrospective study on the prognostic factors and success, survival, and failure outcomes of treated endodontic‐periodontal lesions - Ingar Wong; An Ton; Amiel J. Cassidy; Nicolette Fozzard; Lavanya Ajay Sharma; Robert M. Love; Ajay Sharma (Wiley, 2024)
Abstract Objectives The objective of this retrospective study was to determine possible prognostic factors of endodontic‐periodontal lesions and to compare success, survival, and failure outcomes of treated endodontic‐periodontal lesions across different treatment modalities, demographic variables, and anatomical tooth variations. Materials and Methods Data was collected from patient records in the patient management system (Salud, Titanium Solutions) from the Griffith University Dental Clinic between January 2008 and December 2021. The search strategy used the terms "endodontic periodontal lesion," "periodontal endodontic lesion," "endo perio lesion," "perio endo lesion," and "EPL." The 88 cases which met inclusion and exclusion criteria were analyzed. Results The overall success rate was 46.6%, with 21.6% of teeth surviving and 31.8% of teeth failing. Bone loss extending to the apical third (OR = 0.3, 95% CI [0.104, 0.866]), and probing depths of 5-7 mm (OR = 0.147, 95% CI [0.034, 0.633]) and 8‐10 mm (OR = 0.126, 95% CI [0.029, 0.542]) were associated with a statistically significant lower odds of success (p < .05). A history of no periodontal disease (OR = 7.705, 95% CI [1.603, 37.037]) was associated with a statistically significant higher odds of success (p < .05). Conclusion Practitioners should be aware of bone loss to the apical third, deep probing depths, and a history of periodontal disease as possible prognostic factors that can affect the success rate when treating endodontic‐periodontal lesions. Further research with more stringent control over operator factors should be done to investigate these variables.